2000
DOI: 10.1080/028418600430743
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Radiological Lung Density Changes After Postmastectomy Radiotherapy

Abstract: The purpose of this study was to quantify the time course of radiological lung changes in patients after postmastectomy radiotherapy assessed from routine follow-up chest x-rays. Radiological density changes in the apex of the irradiated lung were quantified by a recent lung densitometry assay. Lung changes were expressed as the so-called Relative change in Equivalent Absorber Thickness (REAT). The clinical series comprised 329 patients treated with postmastectomy radiotherapy between 1978 and 1982. Of these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Unfortunately, it was not successful. These results are different from previous studies (6,7,23,24) on the dose-density relationship of lung after RT. They have established a dosedensity curve and found that with the increase of radiation dose, lung density increases, and this lung density dose-dependent increase has a time-dependent characteristic.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, it was not successful. These results are different from previous studies (6,7,23,24) on the dose-density relationship of lung after RT. They have established a dosedensity curve and found that with the increase of radiation dose, lung density increases, and this lung density dose-dependent increase has a time-dependent characteristic.…”
Section: Discussioncontrasting
confidence: 99%
“…As mentioned above, early studies have confirmed that changes in lung density obtained by quantitative analysis do not necessarily represent the inevitability of RP, and this density change changes with time after RT (7,8,24). Although lung CT imaging is an effective diagnostic tool for RP, it cannot predict the occurrence time of RP in the early stage, which is a difficult problem in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographic abnormalities, indicative of injury, are noted in the lung almost immediately after thoracic RT. 27,37 The radiographic findings most extensively studied are increased density on CT and decreased pulmonary perfusion on SPECT. Radiation dose is the single most important contributor to the development of radiographic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue hypoxia, drugs employed, and genetic features may also affect the clinical tissue radiosensitivity after a normal fractionated schedule. Drugs such as chemotherapy or hormone therapy have been demonstrated to enhance subcutaneous fibrosis after radiotherapy as reported by Skoczylas et al and Bentzen et al who analyzed the impact of adjuvant cyclophosphamide, methotrexate, and fluorouracil (CMF) or tamoxifen on cosmesis 3,4. On the other hand, the use of aromatase inhibitors seems to exert a protective effect on post-radiation-induced lung fibrosis 5.…”
Section: Introductionmentioning
confidence: 97%